Drug markets, travel distance, and violence: testing a typology - Johnson, Lallen T. (Crime & delinquency, 2016)
The factors complicating our understanding of the drugs and violence nexus include the role of community structure and subculture, and situational features of market exchanges. Reuter and MacCoun contribute to the latter by highlighting a typology of market violence. Using distance as a proxy for social ties, the four-market category typology suggests that the mixing of buyers and sellers from various distances has implications for the amount of violence expected to occur within them. This research performs a partial test of that typology using 5 years of arrest and incident data from the Philadelphia Police Department. Multilevel models reveal that compared with markets with local buyers and sellers, those characterized by lengthier travel patterns have significantly higher counts of violent incidents.